Shoulder Dystocia - Michael Fialkow; Thomas Benedetti; Sara Kim (Association of American Medical Colleges, 2011)
Abstract Shoulder dystocia is an obstetric emergency complicating 0.3%-1% of all deliveries. It can lead to permanent disability or death of the neonate and, on occasion, serious morbidity of the mother. Though frequently associated with higher birth weights, 50% of shoulder dystocias occur in normally grown neonates, making prediction of shoulder dystocia difficult. Shoulder dystocia occurs when descent of the neonate's anterior shoulder is obstructed by the mother's pubic symphysis and on occasions when the posterior shoulder is obstructed by the sacral promontory. Because this emergency can occur unpredictably with any pregnancy, all delivery attendants must have an understanding and a management plan for it. This resource is designed to give obstetric care providers an opportunity to train and practice the hand movements required to manage a shoulder dystocia. As severe shoulder dystocia is an uncommon event, a provider may go years without a real-life experience. Safe delivery of an infant suffering a shoulder dystocia requires several crucial steps. Learners in this course appropriately identify shoulder dystocia, call needed backup support, communicate the situation to the mother, perform the steps to relieve the shoulder dystocia, and accurately document the event. One of the great challenges to simulation training is demonstrating the effort put toward simulating clinical care results in a measurable improvement in patient care. Shoulder dystocia simulation is one of the few models that has overcome this challenge. Simulation of shoulder dystocia reduces delivery time, improves timeliness of interventions, and improves performance of the necessary maneuvers. Clinically, this results in a reduction of perinatal asphyxia and neonatal ischemic encephalopathy. The model itself is low tech and reusable, making it ideal for training programs. The significance of our work is that few, if any, research papers studying simulation training provide adequate information about the intervention for educators interested in applying the technology to their training program. Our curriculum provides didactic materials, including video examples on the simulator, and guidelines for administration of a simulated shoulder dystocia event as well as the necessary evaluation forms and documentation.